2020
DOI: 10.1186/s12859-020-03930-7
|View full text |Cite
|
Sign up to set email alerts
|

Inter-protein residue covariation information unravels physically interacting protein dimers

Abstract: Background Predicting physical interaction between proteins is one of the greatest challenges in computational biology. There are considerable various protein interactions and a huge number of protein sequences and synthetic peptides with unknown interacting counterparts. Most of co-evolutionary methods discover a combination of physical interplays and functional associations. However, there are only a handful of approaches which specifically infer physical interactions. Hybrid co-evolutionary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…There are two hypotheses addressing the relative contributions of physical interaction versus co-function to correlated evolutionary rates. The idea that physical interactions contribute more to correlated evolutionary rates hinges on the maintenance of proper binding [11][12][13] . Under this hypothesis, a mutation in one binding partner will result in a compensatory mutation in the other, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…There are two hypotheses addressing the relative contributions of physical interaction versus co-function to correlated evolutionary rates. The idea that physical interactions contribute more to correlated evolutionary rates hinges on the maintenance of proper binding [11][12][13] . Under this hypothesis, a mutation in one binding partner will result in a compensatory mutation in the other, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The most successful have either been restricted to specific proteins, placed cumbersome restrictions on the sequences analyzed, or applied complex models from which biological understanding is hard to extract ( Halperin et al, 2006 ; Gomes et al, 2012 ; Ovchinnikov et al, 2014 ; Jia et al, 2020 ). Machine Learning has demonstrated that co-evolution data, in its entirety, does contain information about structure ( Schaarschmidt et al, 2018 ; Salmanian et al, 2020 ; Li et al, 2021 ). In particular AlphaFold and AlphaFold2 have shown that deep learning that incorporates covariation in homologous sequences can significantly improve the prediction of tertiary structure ( Senior et al, 2020 ; Jumper et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%